PENGHAYATAN HIDUP UMAT PAROKI STA. MARIA ASSUMPTA KEUSKUPAN AGUNG KUPANG TERHADAP KOMUNITAS BASIS GEREJANI MENURUT SIDANG AGUNG GEREJA KATOLIK INDONESIA TAHUN 2000 - Kase, Emanuel B. S.; Tukan, Antonius I. N.; Oetpah, Dorince (Pastoralia Jurnal Penelitian Dosen, 2020)
This research was conducted to find out how deep the faith of the faithful in the Basic Ecclesial Community (BEC) or in Indonesia is called Komunitas Basis Gereani (KBG). This research is a form of concern for the lives of the faithful in the church base community. The Ecclesial Base Community is one of the communities that became a model community that can be a light to illuminate the situation of Indonesian society after the 1998 Reformation. This idea was born from the agreement of the General Assembly of the Indonesian Catholic Church (SAGKI) in 2000. According to the leaders of the Indonesian Catholic Church (Bishops) and representatives of the people present, it was found that the decline in the life of the nation and state that occurred in Indonesia after the Reformation was caused by the decline in the appreciation of faith. Therefore, SAGKI recommended the BEC as a “way” to build a common spirit in advancing the nation. This research is made with a qualitative model. Relevant theories to be used as a framework for thinking and asking questions are also presented in this research. The report on the results of this research is made descriptively, by dividing it into sub-themes according to the classification of questions that have been made.